Why, when and for what diseases pregnant and new mothers “should” be vaccinated - Gabutti, Giovanni (Hum Vaccin Immunother, 2016)
Immunological and serological changes that occur during pregnancy can alter the susceptibility of both the mother and the fetus against various infectious diseases. The pregnant woman has an altered immune response and, for some pathologies, is at increased risk of infection and of developing complications and serious outcomes. In addition, maternal infections can result in congenital anomalies, malformations or severe neonatal diseases. Vaccination of pregnant women can therefore have a double goal: to protect the mother from diseases that could have an impact on her health and to avoid infection/disease transmission to the fetus or the newborn. Despite the potential benefits of immunization in pregnant women, it is still evident reluctance and/or refusal of vaccinations by health professionals as well as by pregnant women, who are wary of the real advantages linked to vaccines. For these reasons a group of experts has evaluated the latest scientific evidence reported in the international literature on this relevant topic.